Dietary mushroom noodles / Nurmaherah Arifin, Nurul Ain Najihah Musa and Nuraliah Aqilah Ayuni Mohamed - Arifin, Nurmaherah; Musa, Nurul Ain Najihah; Mohamed, Nuraliah Aqilah Ayuni (Faculty of Plantation and Agrotechnology, 2023)
This study was designed to develop mushroom-enriched noodles to varying degrees and nutritionally compared to commercially available branded noodles. Pleurotus sajor-caju because their benefits include lowering blood sugar, lowering blood pressure and boosting the immune system against infectious viruses and bacteria, an anti-cancer agent that is also rich in antioxidants. Mushroom noodles can provide a source of fiber, protein and minerals such as calcium, potassium and iron as well as some medicinal effects for consumers. Noodles are one of the best food options for all ages that can be served in many ways. Mushroom noodles are lower in carbs than wheat-only noodles. It is considered as a healthy food because it is low in calories and fat but rich in proteins and dietary fibers. In addition, adding mushrooms to the production of noodles will simultaneously increase the content of protein, fat, fiber, ash, calcium, and iron. These test noodles were developed by mixing mushrooms puree with other ingredients such as flour, salt, and corn starch in different proportions respectively. Other elements such as ionized salt, cornstarch, eggs, and water are kept for all recipes. Moreover, mushroom noodles also have nutritional potential. This result also showed lower levels of carbohydrates, fat and sodium in the tested processed noodles. Thus, mushroom noodles can be a potential superfood.